Curbing Environmental Degradation to Balance Sustainable Development: Evidence from China - Kagzi, Muneza (Archīum Ateneo, 2024)
To achieve the goals of sustainable development, it is crucial to check the balance of increased level of international trade along with financial development, foreign direct investment (FDI), energy consumption, and institutional advancement with the quality of the environment. This study focuses on how these variables have caused environmental degradation in China. To achieve Goal 13 of the Sustainable Development Goals (SDGs), i.e. to increase the nation's resilience to natural disasters and hazards related to climate change, to promote climate action and safeguard life as part of sustainable development, this involves the analysis of time-series data sets from 1975 to 2021 and the use of the dynamic version of ARDL (Autoregressive Distributed Lag) cointegration or simulation model. The results show that FDI is essential for lowering carbon dioxide (CO2) emissions over the long term, but financial development, the volume of international trade, and the level of energy use or consumption contribute to environmental deterioration. Moreover, China's environmental degradation is decreased by high institutional quality. To accomplish the SDGs and reduce environmental degradation, it is essential to take into account how these elements interact and to adopt a holistic strategy that includes regulations, policies, and education. On the basis of our trustworthy findings, suggestions are made to keep the sustainable development.